The Estimation Value of 99mTc-MAA in Comparison with 90Y-PET/MR-based Dosimetry in Selective Internal Radiation Therapy (SIRT) for Liver Malignancies - Yeyin, Nami; Abuqbeitah, Mohammad; Namazova, Aysel; Demir, Mustafa (Current Radiopharmaceuticals, 2025)
AimThis study intended to compare the radiation dose estimates to target and non-target liver compartments from 99mTc-MAA SPECT/CT and 90Y-PET/MR scans in liver tumors treated by 90Y-glass microspheres.Materials and MethodsDose estimation was performed for twenty-three eligible patients (13M, 10F) after 99mTc-MAA simulation using SPECT/CT imaging, and over 90Y-PET/MR images after 90Y-microsphere therapy. Simplicit90Y™ software was used for voxel-based dosimetry over the liver parenchyma. Dose estimates were obtained for whole healthy liver (HL), healthy injected liver (HIL), and tumor volumes. Pearson correlation, Bland–Altman plot, and Wilcoxon signed-ranks test were used for statistical analysis.ResultsThe mean tumor dose was 270 ± 111 Gy, the whole liver parenchyma dose was 26 ± 12 Gy, and the healthy injected liver dose was 55 ± 18 Gy from 99mTc-MAA simulation. 90Y-PET/MR dosimetry yielded a mean tumor dose of 271 ± 125 Gy, a HIL mean dose of 54±18 Gy, and a liver parenchyma dose of 25 ± 12 Gy. An excellent agreement was demonstrated between tumor doses (R2=0.90) and liver doses (R2=0.87), while the agreement was less for HIL doses (R2=0.80). Wilcoxon signed-ranks test yielded no significant difference between the dose estimates for all liver compartments.ConclusionIt was deduced that 99mTc-MAA SPECT/CT simulation provides valuable dose prediction in 90Y-glass microsphere therapy. Despite the difference in volume measurements and dose estimates with 90Y-PET/MR, the predictive value of the 99mTc-MAA simulation was not affected.
Keywords: radioembolization